Money for the issuer: Liability or equity? - Biagio Bossone; Massimo Costa (Economics: The Open-Access, Open-Assessment Journal, 2021)
This study analyzes the nature of money through the lens of the international principles of accounting and lays the foundations of what it calls the accounting view of money (AVM). Using international accounting principles, the AVM argues that the fiat monies issued by the state (typically, cash, banknotes, and central bank money) are not debt and that in fractional reserve regimes, only a share of commercial bank money can be regarded as debt. The AVM argues, instead, that state monies and the nondebt share of commercial bank money are net wealth of their holders and net worth (equity) of their issuers and determines how the seigniorage associated with money issuance should be accounted for correctly in the financial statements of the issuing institutions. The AVM points to the correct way to account for the various forms of money in the financial statements of the issuing institutions, clarifies what the different accounting treatments imply for a correct understanding of the concept of money, and evaluates the related economic and economic policy implications.
Keywords: 330; accounting; central bank money and capital; commercial banks; debt; deposits; equity; payment settlements; seigniorage